Câncer em Fortaleza: morbidade e mortalidade no período 1978-80 - Silva, Marcelo Gurgel Carlos da (1982)
The author talks about the importance of câncer in Public Health on a historie standpoint, analysing the contribution and the participation ofseveral conditioning factors the decline of mortality by infectious diseases, the increase in the average oflife, the urbanization and the industrialization, the introduetion of the carcinogens, the persistence and/or the acquisition of hazardous habits to health, which can be responsible for the increase of malignant neoplasms. The role of Epidemiology was emphasized for the natural history and especially for the determination of the measurements for the control of câncer. The Câncer Registries, basic and essential instruments to the epidemiological investigation of câncer, were judiciously focused under their various types and operational features and also pointed out the general aspects of the functioning of the Câncer Registry of Ceará. The mortality data were taken out from the death certificates of the inhabitants of Fortaleza, obtained in the Epidemiology and Statistics Division of the Ceará Health Secretary, and those of morbidity, through forms of notification ofthe Câncer Registry of Ceará. The death certificates, after the selection of the underlying cause, were codified by the International Classification of Diseases — Revision 1975 and scrutinized by cause, in accordance with the Brazilian List of Mortality, by sex and age groups, in order to, subsequently, determine the corresponding rates of mortality. The forms of notification of câncer were revised and confronted with the files-index of the Câncer Registry of Ceará, to avoid duplicity of notification the intrusion of cases of non-residents in Fortaleza and the erroneous entry of other pathologic conditions. The remainder forms were coded by the International Classification of Diseases — Revision 1975 and verified by anatomic site, sex and age, to determine subsequently the corresponding rates ofincidence. The results of incidence and of mortality were age-standardized by models of population: european, world and african, to permit comparision with data from other places. With the mortality data the role of câncer death was evaluated in the probabilities of death, survival and life expectancy, by sex, age, through multiple decrement life tables. The chief sites of câncer were analysed as to the degree ofimportancein the incidence and mortality, and their rates compared with the statistics of other areas. The epidemiclogic aspects of each malignant neoplasm were discussed. The author concludes that câncer is a major problem of Public Health because it is a disease of increasing magnitude and also because it represents a remarkable cause of mortality, for its elevated economic and social costs, and because of the difficulties and limitations for its control, and, also for its ascending perspective in face of the maintenance of risk factors observed in Fortaleza.